Spatial goals and actions in the orbitofrontal cortex - Bonacchi, N. (2019)
"The orbitofrontal cortex (OFC) is thought to be involved in the representation of anticipated behavioral outcomes that drive goaldirected behavior. Among the properties of goals or outcomes that may be represented in the OFC is their spatial location, a fundamental feature of goals for animals that rely heavily on locomotion for foraging. Previous studies have described neural correlates of choice and goal location in rats performing spatial two-alternative choice tasks. However, relatively little is known about the spatial properties of these OFC neural representations.(...)"